2022
DOI: 10.1039/d2se00658h
|View full text |Cite
|
Sign up to set email alerts
|

Doping-engineered biphenylene as a metal-free electrocatalyst for the hydrogen evolution reaction

Abstract: The rational design of excellent catalytic activity and high chemical stability metal-free electrocatalysts is the core of the large-scale hydrogen production from water splits. Herein, using first-principles calculations, we investigated...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…All the ΔG H* values are larger than 0.40eV except that of H4. The Gibbs free energy, −0.25 eV, for H4 of V 6 C 6−α is close to the recommended HER active center (±0.2 eV) [40]. Therefore, V 6 C 6−α with its surface C at H4 site can be a candidate of HER reactions.…”
Section: Hydrogen Evolution Reaction Activitymentioning
confidence: 63%
“…All the ΔG H* values are larger than 0.40eV except that of H4. The Gibbs free energy, −0.25 eV, for H4 of V 6 C 6−α is close to the recommended HER active center (±0.2 eV) [40]. Therefore, V 6 C 6−α with its surface C at H4 site can be a candidate of HER reactions.…”
Section: Hydrogen Evolution Reaction Activitymentioning
confidence: 63%
“…43 Additionally, Chen et al discovered that doping BPN with B, P, and S elements significantly enhanced its performance in the hydrogen evolution reaction (HER). 44 Feng et al further revealed that precise control of the Mo atom count on BPN leads to the creation of efficient nitrogen reduction reaction (NRR) electrocatalytic materials. 45 Notably, the potential of metal dual-atoms loaded on BPN for CORR catalysis has yet to be deeply explored, presenting a novel direction and strategy for future research.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of carbon-based monatomic catalysts such as two-dimensional (2D) graphene and C 3 N 4 , which have an atom utilization rate close to 100%, opens the way to explore the correlation between the structure and catalytic activity. , Recently, a planar sp 2 -hybridized carbon allotropebiphenylene network (BPN) was synthesized on the gold (111) surface by Gottfried et al, marking the introduction of a novel 2D carbon material constituted by tetra (C4), hexa (C6), and octa (C8) carbon rings . The distinctive metallic attributes coupled with positively charged carbon atoms in the tetra rings augment the binding strength with reaction intermediates, thereby enhancing the interfacial activity of BPN. Liu et al found that biphenylene exhibited excellent catalytic activity during oxygen reduction reaction (ORR) under alkaline conditions . However, the catalytic performance of a single biphenylene is still far from that of commercial platinum metal catalysts.…”
Section: Introductionmentioning
confidence: 99%